Large‐Scale Ultrathin 2D Wide‐Bandgap BiOBr Nanoflakes for Gate‐Controlled Deep‐Ultraviolet Phototransistors. Issue 12 (19th February 2020) - Gong, Chuanhui; Chu, Junwei; Qian, Shifeng; Yin, Chujun; Hu, Xiaozong; Wang, Hongbo; Wang, Yang; Ding, Xiang; Jiang, Shangchi; Li, Alei; Gong, Youpin; Wang, Xianfu; et al.
Abstract: Ternary two‐dimensional (2D) semiconductors with controllable wide bandgap, high ultraviolet (UV) absorption coefficient, and critical tuning freedom degree of stoichiometry variation have a great application prospect for UV detection. However, as‐reported ternary 2D semiconductors often possess a bandgap below 3.0 eV, which must be further enlarged to achieve comprehensively improved UV, especially deep‐UV (DUV), detection capacity. Herein, sub‐one‐unit‐cell 2D monolayer BiOBr nanoflakes (≈0.57 nm) with a large size of 70 µm are synthesized for high‐performance DUV detection due to the large bandgap of 3.69 eV. Phototransistors based on the 2D ultrathin BiOBr nanoflakes deliver remarkable DUV detection performance including ultrahigh photoresponsivity ( R λ, 12739.13 A W −1 ), ultrahigh external quantum efficiency ( EQE, 6.46 × 10 6 %), and excellent detectivity ( D *, 8.37 × 10 12 Jones) at 245 nm with a gate voltage ( V g ) of 35 V attributed to the photogating effects. The ultrafast response (τrise = 102 µs) can be achieved by utilizing photoconduction effects at V g of −40 V. The combination of photocurrent generation mechanisms for BiOBr‐based phototransistors controlled by V g can pave a way for designing novel 2D optoelectronic materials to achieve optimal device performance. Abstract : Sub‐one‐unit‐cell two‐dimensional (2D) BiOBr nanoflakes are controllably synthesized by chemical vapor deposition (CVD). BiOBr‐based phototransistors demonstrate distinguished deep‐ultraviolet (DUV) detection performance, including ultrahigh photoresponsivity, external quantum efficiency, and detectivity, as well as ultrafast response, which depends on regulatable evolution between the photoconduction effect and the photogating effect by the gate voltage.